1984
DOI: 10.1159/000153486
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Groups and Leukemia

Abstract: Haptoglobin groups were studied in 100 leukemia patients and controls. Previously reported associations with Hp1-1 and the Hp1 gene by other investigators were not confirmed. In agreement with a previous observation a significant increase of ahaptoglobinemia (Hp0) was found among the leukemia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
7
1
Order By: Relevance
“…In contrast, ahaptoglobinemia was more frequent among these patients, in agreement with the findings of Fröhlander (1984). Calderoni et al (2006) investigated the frequency of Hp phenotypes in patients suffering from indeterminate, chronic cardiac, chronic digestive or chronic 'combined' (i.e.…”
Section: Association Studies In Brazilian Populationssupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, ahaptoglobinemia was more frequent among these patients, in agreement with the findings of Fröhlander (1984). Calderoni et al (2006) investigated the frequency of Hp phenotypes in patients suffering from indeterminate, chronic cardiac, chronic digestive or chronic 'combined' (i.e.…”
Section: Association Studies In Brazilian Populationssupporting
confidence: 79%
“…A significantly higher frequency of the Hp1-1 phenotype was observed among leukemia patients with ALL, AML and CML, but not among those with CLL. Fröhlander (1984) found no association between Hp phenotypes and leukemia but observed a significantly higher frequency of ahaptoglobinemia in these patients. A low Hp2-2 frequency has been observed in patients with IgA myeloma (Germenis et al, 1983).…”
Section: Cancercontrasting
confidence: 59%
“…Earlier studies on the possible associa tion between serum HP and leukaemia [Latner and Zaki, I960;Galatius-Jensen, 1962;Peacock, 1966;Papiha et a!., 1974;Naik et al, 1979 andFrohlander, 1984] had reported an increased frequency of HP1 in patients compared with controls, but in only two [Latner and Zaki, 1960;Peacock, 1966] did it reach the level of sig nificance.…”
Section: Introductionmentioning
confidence: 95%
“…How ever, only the three main phenotypes have been considered in such studies [Frohlander, 1984;Matsuyama and Joseph, 1984;Norrgard et al, 1984], Genes influence lipid levels and athero sclerosis risk [Berg, 1983[Berg, , 1985 and the identification of the individual genes in question is an important task. Sing and Orr [1976] analysed the effect of the main Hp types on total cholesterol level and found that females with genotype Hp2-2 had on average a 4.22mg/100ml (0.11mmol/l) higher cholesterol level than females possessing the Hpl gene.…”
Section: Introductionmentioning
confidence: 99%